An Ethical Framework for Hacking Operations. - Bellaby, Ross W. (Ethical Theory & Moral Practice, 2021)
In recent years the power and reach of prominent hacker groups such as Anonymous and LulzSec has been clearly demonstrated. However, in a world where hackers are able to wield significant online power, can they do so ethically as legitimate agents? To answer this question this paper will develop an ethical framework based on the premise that hackers have exhibited instances where they have acted to protect people from harm at a time when there was no one else to do so. At its core this paper will argue that political hacking can be justified when it is done to protect the vital interests of oneself or others. Moreover, it will also argue that just because hackers are outside the state does not automatically discount them as ethical actors and that when the state fails to protect people – whether it is due to a lack of ability, political will or because the state is the source of the threat – hackers can fill the void. In order to achieve this, first it is necessary to highlight the space for hackers to operate; second, guide hacker activity by creating an ethical framework detailing what actions are justified towards what end; third, to offer mechanisms that can aid in reaching these ethically justified decisions; and as a result, inform further ethical debates on how to react to these political hackers. This means that the framework can be used to both justify and condemn hacking depending on the circumstances, allowing those on the outside to distil and evaluate a political hack, both past and present, while guiding hacker collectives by providing clearer ethical tools for determining the appropriate agendas and methods.